Evaluation of E-VAKU Application Usability using System Usability Scale and Cognitive Walkthrough Methods - I Made Reyvinno Dirga Narke; Deny Wiria Nugraha (SISTEMASI, 2026)
The Central Sulawesi Provincial Government, in line with digital transformation and e-government initiatives, has implemented the E-VAKU application (Electronic Financial Accountability Verification). This digital system is designed to address bureaucratic challenges and enhance efficiency and transparency in the verification of regional financial accountability. Given that the success of an information system is strongly influenced by its usability, this study conducts a comprehensive usability evaluation of the E-VAKU application using a combination of two methods. The System Usability Scale (SUS) is employed to quantitatively measure user perceptions, while the Cognitive Walkthrough (CW) method is applied to identify specific issues within workflows and user interface interactions. The SUS evaluation produced an average score of 74.25, which falls into the “Good” category with a grade of B. Meanwhile, the CW analysis recorded a success rate of 90%, an error rate of 12%, and a time-based efficiency of 0.0205 tasks per second. The findings from both methods resulted in specific improvement recommendations, including interface redesigns for the onboarding, login, dashboard, and Payment Order (SPP) pages, as well as the addition of notification and search features. These enhancements aim to make the E-VAKU application more intuitive and user-friendly. This study is expected to serve as a practical reference for developers in refining the application to support more effective and optimal governance practices.